Association Between Family Atmosphere and Internet Addiction Among Adolescents: The Mediating Role of Self-Esteem and Negative Emotions - Yijian Shi; Zijun Tang; Zhilin Gan; Manji Hu; Yang Liu (Frontiers Media S.A., 2023)
Objectives: Family atmosphere is a significant predictor of internet addiction in adolescents. Based on the vulnerability model of emotion and the compensatory internet use theory, this study examined whether self-esteem and negative emotions (anxiety, depression) mediated the relationship between family atmosphere and internet addiction in parallel and sequence.Methods: A total of 3,065 Chinese middle school and high school students (1,524 females, mean age = 13.63 years, SD = 4.24) participated. They provided self-reported data on demographic variables, family atmosphere, self-esteem, anxiety, depression, and internet addiction through the Scale of Systemic Family Dynamic, Self-Esteem Scale, Self-Rating Anxiety Scale, Self-Rating Depression Scale, and Internet Addiction Test, respectively. We employed Hayes PROCESS macro for the SPSS program to scrutinize the suggested mediation model.Results: It revealed that self-esteem, anxiety, and depression mediated the relationship between family atmosphere and internet addiction in parallel and sequence. The pathway of family atmosphere-self-esteem-internet addiction played a more important role than others.Conclusion: The present study confirmed the mediating role of self-esteem and negative emotions between family atmosphere and internet addiction, providing intervention studies with important targeting factors.